Comparative Analysis of the Application of Corporate Income Tax Between Based on the Income Tax Law Number 36 of 2008 with Government Regulation Number 23 of 2018 on CV. ITM - I G A Okta Nia Pramesthi; N S Hardika; W Purwanta Suta (Jurusan Akuntansi Politeknik Negeri Bali, 2020)
Micro, Small, and Medium Enterprises (MSMEs) taxpayers with a gross circulation of up to IDR 4.800.000.000,00 are given the facility to choose the tax rate used to calculate the income tax payable. MSMEs taxpayers can choose to use income tax calculations based on Income Tax Law Number 36 of 2008 or Government Regulation Number 23 of 2018. This study aims to determine the comparison of the calculation of the tax payable on the owed entity on the CV. ITM which is a company engaged in catering services using calculations by the income tax calculation based on the Income Tax Law Number 36 of 2008 and Government Regulation Number 23 of 2018 to find out the most appropriate and profitable method to efficiency corporate income tax. The data used in this research are secondary data collected through documentation techniques. The data analysis technique used in this research is a descriptive quantitative analysis technique. The results showed the CV. ITM is more efficient to use tariffs by Government Regulation No. 23 of 2018 to calculate the amount of corporate income tax because it can streamline the corporate income tax.